Application of the rapid thermal treatment for annealing the ion-doped layers of polysilicon - Anishchik, Victor M.; Harushka, Valiantsina A.; Pilipenka, Uladzimir A.; Ponariadov, Vladimir V.; Saladukha, Vitali A. (Journal of the Belarusian State University. Physics, 2017)
The possibility to apply the rapid thermal treatment procedure for the formation of ion-doped layers in polycrystalline silicon is considered. It is demonstrated that such rapid thermal treatment allows one to reduce redistribution of the implanted admixture, to make its electric activation more complete. The accelerated diffusion process of the admixture implanted into polycrystalline silicon with the use of the intense light flux is consistently explained.
Keywords: rapid thermal treatment; polycrystalline silicon; ion-doped layer; surface resistance